A collection assessment of Bachelor of Sports Science in College of Human Kinetics Library in the University of the Philippines Diliman - Eugenio, Lucan L.; Obille, Kathleen Lourdes B. (Quezon City School of Library and Information Studies, University of the Philippines Diliman, 2018)
Every library should conduct a periodic collection assessment to ensure that their collection is up-to-date and relevant to the needs of their users. Collection assessment provides an organized analysis that helps librarians to improve its library collection in line with the users' needs.
The main objective of this study is to make sure that the UP College of Human Kinetics Library provides a good collection of Sports Science students by conducting collection assessment. This study sought to determine if the users of the library satisfied with the collection. It also determined the strengths and weaknesses of the collection by mapping it against the Sports Science curriculum. The librarian also interviewed for supplementary information as regards to the collection development efforts of the UP College of Human Kinetics Library.
The data gathered from the collection mapping showed that there are 6,436 titles available in the collection. This revealed that there is a strong support to the subject areas like Anatomy and Physiology, Sports Psychology, Conditioning and First Aid, and Coaching. On the other hand, library collection's weakness are the subject areas for the electives in Fitness Dance, electives in Weight training, and Ergonomics. It is also revealed that the quality of books may be considered irrelevant because almost half of the collection was published in 1980 and below.
Based on the results of the survey, the researcher found out that majority of the students and faculty visit the CHK Library. The purpose of the library users, both students and faculty, is for their academic needs. Overall, the respondents of the survey were satisfied with the library collection and rated it as adequate since they thought that the collection appropriate and supported their academic needs.
The study provides recommendations to further improve the CHK Library and its collection. This includes that the librarians should at least weed out some materials that are not relevant to the collection. It is also recommended that the faculty submit their updated syllabi as basis for references to be acquired. Furthermore, the library should maintain strong support for the subject areas like Conditioning and First Aid, Coaching, and Anatomy and Physiology. On the other hand, improve the electives subject areas by acquiring new materials.
Thesis
Keywords: University of the Philippines (Diliman) -- College of Human Kinetics Library; Collection development (Libraries) -- Evaluation